MENINGKATKAN MOTIVASI BELAJAR MELALU VIDEO INTERAKTIF PADA MATA PELAJARAN PENDIDIKAN PANCASILA DIKELAS 5 SD NEGERI 1 TATURA - Melinda Supratman; Sri Mulyani; Deitasmalina Musa (EDU RESEARCH, 2024)
Student learning motivation is one of the important factors that influence success in the learning process, especially in mathematics subjects that are often considered difficult by students. In grade V of SD Negeri 1 Tatura, student learning motivation is still low, so efforts are needed to increase their motivation. One potential approach is the application of interactive video media such as YouTube which is expected to attract students' interest and facilitate visual understanding of concepts. This study aims to increase the learning motivation of grade V students of SDN 1 Tatura in Pancasila Education learning through the application of interactive video media. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles. Each cycle includes the planning, implementation, observation, and reflection stages. Student learning motivation is measured through observations of five indicators: interest and passion for learning, active involvement in class, response to feedback, enthusiasm in learning, and perseverance and consistency in learning. The results of the study showed a significant increase in student learning motivation. The average student learning motivation increased from 51% in the pre-cycle to 77% in cycle I, and reached 91% in cycle II. This increase is seen in all indicators, especially in the aspects of interest, active involvement, and response to feedback. Interactive video media has proven effective in increasing students' learning motivation in Pancasila Education subjects. The use of this media not only increases students' involvement in the learning process, but also helps them understand abstract concepts. It is recommended that this media be used sustainably and integrated with other learning strategies to maximize student learning outcomes.